Peripheral Microcirculation and Endothelial Function in Comas Induced by Acute Cerebrovascular Accident - S. L Kan; Yu. A. Churlyaev; D. G Dantsiger; A. A. Kosovskikh; A. V. Ekimovskikh; P. G. Sitnikov (Общая реаниматология)
Objective: to study the state of systemic microcirculation and endothelial function in comas induced by acute cerebrovascular accident (ACA). Subjects and methods. The study was conducted within the first 7 days of ACA in 38 coma patients, who were divided into groups according to the etiology of stroke: Group 1 comprised 20 patients with hemorrhagic stroke; their mean age was 56.6±2.3 years; Group 2 consisted of 18 patients with ischemic stroke; their mean age was 58.5±2.2 years. A control group included 34 apparently healthy individuals; their mean age was 55.1±2.1 years. The microcirculatory bed was evaluated within 7 days, by applying cutaneous laser Doppler flowmetry using a LAKK-02 capillary blood flow laser analyzer made in Russia (LAZMA Research-and-Production Association, the Russian Federation). Coincidentally with recording of the microcirculatory blood flow, blood samples were collected to explore the serum concentrations of endothelin-1, stable nitric oxide metabolites, van Willebrand factor, and thrombomodulin. Results. Throughout the study, the patients with coma induced by ACA were found to have microcirculatory disorders consisting in higher microperfusion along with the markedly increased influence of active modulators of vascular tone, as well as endothelial functional structural changes. Conclusion. The data obtained in the study suggest that there were uniform changes in the state and regulation of systemic microcirculation in patients with ACA irrespective of the type of stroke (hemorrhagic or ischemic). Key words: stroke, microcirculation, microvascular bed, micro blood flow, tissue perfusion, endothelium.